Factors Influencing the Realization of Smart and Comfortable City Development Study of Balikpapan City - Suharto, Rahcmad Budi; Mas’ud, Rahmad; Jiuhardi, Jiuhardi; Roy, Juliansyah (International Journal of Economics (IJEC), 2025)
This study aims to determine and analyze the influence of health factors, education, infrastructure availability and minimum wages on labor absorption both directly and through private investment and economic growth. This study uses secondary data in the form of life expectancy data, average length of schooling, distributed energy, provincial minimum wages, private investment (PMA and PMDN), GRDP, economic growth, and the number of working population in each province in Eastern Indonesia. The data is in the form of N The results of the study show that directly health factors, education, and provincial minimum wages have a negative and significant effect on labor absorption while infrastructure availability has a positive and significant effect. Indirectly health factors, infrastructure availability and minimum wages are able to increase labor absorption both through investment and economic growth in contrast to the education factor which has not maximized labor absorption both through investment and economic growth. This is in line with the conditions of KTI which are still dominated by informal sector employment.